AN ANALYSIS OF EDUCATIONAL VALUES OF THE NOVEL “ SILENT PATIENT ” BY ALEX MICHAELIDES - Dini Anggriani; Clarry Sada; Eni Rosnija (Universitas Tanjungpura, 2022)
The low interest in reading in Indonesia threatens the quality of the young generation who hold Indonesia's future. Stimulating interest in reading can be done through reading materials that are popular among students, such as psychological thriller novels. Thus, researchers must encourage students to use English novels as reading material. This study aimed to determine the workability of the novel The Silent Patient by Alex Michaelides as reading material for EFL students. This study of